ERV1 Overexpression in Myeloid Cells Protects against High Fat Diet Induced Obesity and Glucose Intolerance. Issue 1 (December 2017) - Sima, Corneliu; Montero, Eduardo; Nguyen, Daniel; Freire, Marcelo; Norris, Paul; Serhan, Charles; Van Dyke, Thomas
Abstract Non-resolving inflammation is a central pathologic component of obesity, insulin resistance, type 2 diabetes and associated morbidities. The resultant hyperglycemia is deleterious to the normal function of many organs and its control significantly improves survival and quality of life for patients with diabetes. Macrophages play critical roles in both onset and progression of obesity-associated insulin resistance. Here we show that systemic activation of inflammation resolution prevents from morbid obesity and hyperglycemia under dietary overload conditions. In gain-of-function studies using mice overexpressing the human resolvin E1 receptor (ERV1) in myeloid cells, monocyte phenotypic shifts to increased patrolling-to-inflammatory ratio controlled inflammation, reduced body weight gain and protected from hyperglycemia on high-fat diet. Administration of a natural ERV1 agonist, resolvin E1, recapitulated the pro-resolving actions gained by ERV1 overexpression. This protective metabolic impact is in part explained by systemic activation of resolution programs leading to increased synthesis of specialized pro-resolving mediators.